Global Mobility of Highly Skilled People Multidisciplinary Perspectives on Self-initiated Expatriation - Habti, Driss; Elo, Maria; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume examines self-initiated expatriates (SIEs), the category of highly skilled people whose movement from one country to another is by choice. Although they are not forced to relocate due to work, conflict or natural disaster, their migration pattern is every bit as complex. The book challenges previous theoretical approaches that take for granted a more simplistic view of this population, and advances that mobility of SIEs relates to the expatriates themselves, their conditions and the different structures intervening in their career life course. With their visible increase worldwide, this book positions itself as a nexus for this on-going discussion, while linking self-initiated expatriation to the theoretical landscape of international skilled migration and mobility. Major interests that catch attention are transnational practices, work-related experiences and personal life course, including forms of inequalities in their migration experiences. The book identifies forms and drivers of migratory behaviour and provides an argument concerning the broader processes of mobility and integration. As such, this book constitutes a departure point for future research in terms of theoretical underpinnings and empirical rigor on global highly skilled mobility of SIEs. The collection of empirical case studies offers an insightful analysis for policy makers, concerned stakeholders and organizations to better cope with this form of migration. .
1. Rethinking Self-initiated Expatriation in International Highly Skilled Migration Driss Habti and Maria Elo -- Part I: Self-initiated Highly Skilled Expatriates and Assigned Expatriates: Recent Developments: 2. Careers of Highly Educated Self-initiated Expatriates: Observations from Studies among Finnish Business Professionals Chris Brewster, Liisa Mäkelä and Vesa Suutari -- 3. Local language acquisition among organizational and self-initiated Finnish expatriates in China Ling Eleanor Zhang and Jakob Lauring -- Part II: Emerging Drivers and Migration Dynamics of Highly Skilled Expatriates: 4. Dynamics of Diasporic Life - Entry and Exit Behavior of Highly Skilled Self-initiated Expatriates Maria Elo and Johanna Leinonen -- 5. Mapping drivers of Arab highly skilled self-initiated expatriation to Finland: Personal-professional life pendulum Driss Habti -- 6. How far can talent take you? Polish skilled mobility as self-initiated expatriation during and after the Cold War Anna Matyska -- Part III: Integrated Networking and Capital mobilization: Relational Dynamics among Highly skilled Expatriates: 7. Together or Alone Together in Ethnically Diverse Work Communities: High-Skilled Expatriates and Social Networking in Finland Aini Pehkonen -- 8. Finnish Citizens' Encounters with the Social and Spatial Environment in Indian Mega-cities Nicol Saventti -- 9. Coping with the boundaryless career: Focus on Finnish self-initiated expatriates in Poland Malla Mattila, Hanna salminen, Anna Astahova -- Part IV: Embedding Place and Process of Integration and Adjustment: 10. Finnish Expatriates in Brussels: Dimensions and Types of Adaptation Johanna Saarentalo-Vuorimäki -- 11. What about 'expatriate children'? Child-level perspective on self-initiated expatriation of Finns Abroad Anu Warinowski -- 12. Self-initiated Expatriates and their Legal Rights in Finland: Incentives and Obstacles to Recruitment and Retention Jaana Palander -- 13. Self-initiated Expatriation Rebooted: A Puzzling Reality - a Challenge to Migration Research, and its Future Direction Maria Elo and Driss Habti. .
Keywords: Emigration and immigration; Population -- Economic aspects; International business enterprises; Human Migration; Population Economics; International Business